Unhealthy family functioning is strongly associated with warfighter brain health following traumatic brain injury in United States service members and veterans - Brickell, Tracey A.; French, Louis M.; Ivins, Brian J.; Lippa, Sara M.; Wright, Megan M.; Baschenis, Samantha M.; Sullivan, Jamie K.; Hungerford, Lars D.; Lange, Rael T. (Frontiers in Neurology, 2025)
ObjectiveTo examine the relationship between family functioning and health-related quality of life (HRQOL) outcomes following traumatic brain injury (TBI) in service members and veterans (SMVs).ParticipantsParticipants were 359 United States SMVs classified into three groups: non-injured controls (NIC, n = 62); uncomplicated mild TBI (MTBI; n = 189); and complicated mild, moderate, severe, and penetrating TBI (STBI; n = 108). Participants completed 10 HRQOL measures from the TBI-QOL and Neuro-QOL, and the Family Assessment Device-General Functioning subscale (FAD-GF) 2-or-more years post-injury. Using the FAD-GF, the NIC, MTBI, and STBI participants were divided into six subgroups: Group 1 = NIC Healthy Family Functioning (HFF) (n = 34); Group 2 = NIC Unhealthy Family Functioning (UnHFF) (n = 28); Group 3 = MTBI HFF (n = 88); Group 4 = MTBI UnHFF (n = 101); Group 5 = STBI HFF (n = 58); and Group 6 = STBI UnHFF (n = 50).ResultsParticipants with UnHFF had a significant and meaningfully higher number of clinically elevated HRQOL scores compared to those with HFF in the MTBI (p < 0.001, ηp2=0.07) and STBI (p = 0.001, ηp2=0.10) groups, but not in the NIC group (p = 0.107, ηp2=0.04). There were no differences in the total number of clinically elevated HRQOL scores when comparing the MTBI and STBI HFF groups to controls (p = 0.074 to 0.841). The MTBI and STBI UnHFF groups had a significant and meaningfully higher number of clinically elevated HRQOL scores when compared to controls (p < 0.001 to p = 0.018; ηp2=0.07 to.14). The MTBI UnHFF group was 10 to 28 times more likely to have poor HRQOL outcome compared to controls. The STBI UnHFF group was 6 to 17 times more likely to have poor HRQOL outcome compared to controls.ConclusionUnHFF was strongly associated with poor long-term HRQOL. HFF was strongly associated with good long-term HRQOL outcome. Assessment and management of family distress may facilitate better TBI recovery and readiness in warfighters.